Orthosilicic acid, Si(OH)4, stimulates osteoblast differentiation in vitro by upregulating miR-146a to antagonize NF-κB activation. (15th July 2016) - Zhou, Xianfeng; Moussa, Fouad M.; Mankoci, Steven; Ustriyana, Putu; Zhang, Nianli; Abdelmagid, Samir; Molenda, Jim; Murphy, William L.; Safadi, Fayez F.; Sahai, Nita
Graphical abstract: Abstract: Accumulating evidence over the last 40 years suggests that silicate from dietary as well as silicate-containing biomaterials is beneficial to bone formation. However, the exact biological role(s) of silicate on bone cells are still unclear and controversial. Here, we report that orthosilicic acid (Si(OH)4 ) stimulated human mesenchymal stem cells (hMSCs) osteoblastic differentiation in vitro . To elucidate the possible molecular mechanisms, differential microRNA microarray analysis was used to show that Si(OH)4 significantly up-regulated microRNA-146a (miR-146a) expression during hMSC osteogenic differentiation. Si(OH)4 induced miR-146a expression profiling was further validated by quantitative RT-PCR (qRT-PCR), which indicated miR-146a was up-regulated during the late stages of hMSC osteogenic differentiation. Inhibition of miR-146a function by anti-miR-146a suppressed osteogenic differentiation of MC3T3 pre-osteoblasts, whereas Si(OH)4 treatment promoted osteoblast-specific genes transcription, alkaline phosphatase (ALP) production, and mineralization. Furthermore, luciferase reporter assay, Western blotting, enzyme-linked immunosorbent assay (ELISA), and immunofluorescence showed that Si(OH)4 decreased TNFα-induced activation of NF-κB, a signal transduction pathway that inhibits osteoblastic bone formation, through the known miR-146a negative feedback loop. Our studies established a mechanism for Si(OH)4 to promote osteogenesis by antagonizing NF-κB activation via miR-146a, which might be interesting to guide the design of osteo-inductive biomaterials for treatments of bone defects in humans. Statement of Significance: Accumulating evidence over 40 years suggests that silicate is beneficial to bone formation. However, the biological role(s) of silicate on bone cells are still unclear and controversial. Here, we report that Si(OH)4, the simplest form of silicate, can stimulate human mesenchymal stem cells osteoblastic differentiation. We identified that miR-146a is the expression signature in bone cells treated with Si(OH)4 . Further analysis of miR-146a in bone cells reveals that Si(OH)4 upregulates miR-146a to antagonize the activation of NF-κB. Si(OH)4 was also shown to deactivate the same NF-κB pathway to suppress osteoclast formation. Our findings are important to the development of third-generation cell-and gene affecting biomaterials, and suggest silicate and miR-146a can be used as pharmaceuticals for bone fracture prevention and therapy.